2016
DOI: 10.1021/acs.langmuir.6b00721
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis of the Contact Angle of a Meniscus Inside a Capillary with Smooth, Homogeneous Solid Walls

Abstract: Citation: KUCHIN, I. and STAROV, V., 2016. Hysteresis of the contact angle of a meniscus inside a capillary with smooth, homogeneous solid walls.Langmuir: the ACS journal of surfaces and colloids, 32(21), pp. 5333-5340.Additional Information: θ , advancing, a θ , and equilibrium, e θ contact angles in thin capillaries were calculated based on the shape of disjoining/conjoining pressure isotherm. It was shown that both advancing and receding contact angles depend on the capillary radius. The suggested mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…40,69 Another manifestation of the first-order wetting transition is the contact angle hysteresis, mainly dominated by surface roughness and chemical heterogeneity, but on flat homogeneous surfaces also a direct consequence of the first-order nature of wetting transitions. 37,[70][71][72] Figure 9 shows the reduction of the wetting coefficient versus the film thickness at different RHs for three surface polarities. Higher RHs lead to thicker water films as well as smaller wetting coefficient k w of the surface.…”
Section: Wetting Off Coexistencementioning
confidence: 99%
“…40,69 Another manifestation of the first-order wetting transition is the contact angle hysteresis, mainly dominated by surface roughness and chemical heterogeneity, but on flat homogeneous surfaces also a direct consequence of the first-order nature of wetting transitions. 37,[70][71][72] Figure 9 shows the reduction of the wetting coefficient versus the film thickness at different RHs for three surface polarities. Higher RHs lead to thicker water films as well as smaller wetting coefficient k w of the surface.…”
Section: Wetting Off Coexistencementioning
confidence: 99%
“…Hence the meniscus gets stuck or pinned at the hardly smooth natural surface of the solid. This pinning phenomenon or formally contact line pinning (CLP) causes the contact angle hysteresis (a difference between the maximum and minimum h) [44]. Contact angle hysteresis, therefore, suggests that there is no unique value for contact angle even at static equilibrium [45].…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…However, these are not the only causes for the existence of contact angles hysteresis. Lately researchers have illustrated that hysteresis exist on smooth homogeneous solid substrates [38][39][40]. It has been observed that contact angle hysteresis on a rigid substrate is dependent on surface forces action in the vicinity of the three-phase contact line [16].…”
Section: Theoretical and Experimental Analysismentioning
confidence: 99%